COMPLEX ORGANIZATION OF MITOTIC APPARATUS - Gasyuk А.P.; Vynnyk N.І.; Гасюк, Д.Ю. (World of Medicine and Biology, 2016)
Cell division is one of the most important biological phenomena, causing the reproductive process. It is this phenomenon that provides the continuous existence of generations of cells and the whole organisms. The most common form of division is mitosis. It encompasses such major processes as the dna reduplication, synthesis of the protein component of chromosomes and achromatin apparatus, doubling of the cytocentrums and formation of the energy storage, required for the mitotic division. Mitotic apparatus is a temporary structure of the cell, which ensures the movement of chromosomes during the cell division (mitosis). Current publications on the complex organization of the kinetochore and centrosome, which is a “cellular process” that manages the dynamics of the morphology of cell, as well as the regulator of the mitotic cycle, have been analyzed. Kinetochores are distinguished as the locus in quo of the mitotic assemblage control point of the cleavage spindle and are represented as the protein structures that ensure the attachment of microtubules of centrosomes and mitotic apparatus during the mitosis.